Experimental and analytical investigations on seismic behavior of non-rectangular reinforced concrete squat walls - Ma, Jiaxing (2017)
Non-rectangular reinforced concrete (RC) squat walls are widely used in existing buildings and safety-related nuclear facilities. Compared with rectangular walls, these walls possess significant stiffness in both principal directions, which contributes to their resistance to biaxial bending actions during earthquakes. In spite of their popularity and practicability, the experimental data on these non-rectangular RC squat walls are rather sparse, especially for walls subjected to non-principal bending action. Moreover, current design procedures are developed for rectangular slender walls, which have been found by many researchers to be unsuitable for non-rectangular RC squat walls. To improve the understanding of the seismic behavior of such walls, both experimental and analytical investigations are conducted in this study.